The description of students’ mathematical problem-solving skill and self-regulation - Ani Nurwijayanti; Akhmad Jazuli; Erni Widyastuti (International Journal of Science and Applied Science: Conference Series, 2017)
The research aimed to describe the students’ mathematics problem-solving skill and self-regulation in SMP Negeri 8 Purwokerto used Miles and Huberman’s model of cover reduction, serve, and conclusion. The data source of this research were eight graders of class F by using purposive sampling. The students grouped into three categories according to the mid-term result. The categories were: high, mediocre, and low scores. The data was collected using tests, questionnaire, interview, and documentation. This research concluded that the students’ mathematics problem-solving skill from those three categories was different. The high score students’ group had a better problem-solving skill compared to the students in the mediocre or the low categories. However, the self-regulation from these three groups did not have a significant difference. It was still at the developing level. Thus, it could be concluded that the students’ self-regulation did not affect the ability to solve mathematical problems.